1991
DOI: 10.1152/jappl.1991.71.6.2346
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and responsiveness of isolated coronary arteries

Abstract: Exercise is associated with release of catecholamines and vasoactive intestinal polypeptides. Recurrent exposure to catecholamines modifies the sensitivity of adrenoceptors. To test the hypothesis that exercise training may affect the sensitivity of the epicardial coronary arteries, we performed studies on isolated coronary arteries from male dogs capable of running on a treadmill. The animals were separated randomly into two groups: sedentary and exercise training. After 11 wk, rings of left circumflex and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 0 publications
2
29
1
1
Order By: Relevance
“…A similar finding using noradrenaline and KC1 was reported in exercise training ofYucatan miniature swine (Oltman et al, 1992). In the dog, however, Rogers et al (1991) demonstrated that contractile responses of the endothelium-intact epicardial coronary arteries (rings) to noradrenaline and phenylephrine were not different between exercised and sedentary control dogs. In exercise trained rats (both running and swimming) Edwards et al (1985) reported no changes in contractile responses to noradrenaline of endothelium-intact thoracic helical strips between those obtained from exercise trained and sedentary control rats.…”
Section: Discussionsupporting
confidence: 83%
“…A similar finding using noradrenaline and KC1 was reported in exercise training ofYucatan miniature swine (Oltman et al, 1992). In the dog, however, Rogers et al (1991) demonstrated that contractile responses of the endothelium-intact epicardial coronary arteries (rings) to noradrenaline and phenylephrine were not different between exercised and sedentary control dogs. In exercise trained rats (both running and swimming) Edwards et al (1985) reported no changes in contractile responses to noradrenaline of endothelium-intact thoracic helical strips between those obtained from exercise trained and sedentary control rats.…”
Section: Discussionsupporting
confidence: 83%
“…Besides, canine coronary smooth muscle has been reported to have a lowered responsiveness to vasoactive relaxants after training. 16 Therefore, the enhanced ACh-induced vasorelaxation response was probably not due to an increased sensitivity of vascular smooth muscle to EDRF.…”
Section: Discussionmentioning
confidence: 94%
“…According to the above studies, we speculated that regular aerobic exercise may enhance endothelium-dependent vasorelaxation. In 1991, Rogers et al 16 found a decrease in responsiveness of canine coronary vascular smooth muscle to vasoactive relaxants after exercise training. However, no reports indicate whether endotheliumdependent vasorelaxation response would be altered by exercise training.…”
mentioning
confidence: 99%
“…Franke et al (22) found that ExT enhanced eNOS-dependent increases in forearm vascular conductance but did not alter vascular responses to eNOS-dependent agonists. In addition, Oltman et al (47) found that ExT did not influence NOS-dependent responses of porcine coronary arteries, and Rogers et al (53) report that ExT actually decreased responsiveness of isolated canine coronary arteries to ␤-adrenergic agonists. Furthermore, we have reported that ExT does not alter eNOS-dependent dilation of the basilar artery in nondiabetic rats (43).…”
Section: Discussionmentioning
confidence: 99%